SPIRITUALITY-BASED LEADERSHIP AS A NURSE'S FOUNDATION: LESSONS FROM THE LIFE OF POPE FRANCIS - Sius, Usu; Dwi Putri, Angela; Urbanus, Urbanus (Jurnal Keperawatan dan Kesehatan, 2025)
The aim is to explore and understand the concept of spirituality-based leadership by analyzing the life and leadership of Pope Francis, as well as the spiritual principles he adheres to. The background of the importance of spiritual values ​​in a nurse's leadership, especially in facing moral and ethical challenges in the modern era, in providing nursing care services. The method used is a qualitative analysis of book and journal literature. The analysis was conducted to identify the leadership principles employed by Pope Francis and their relevance in the leadership context. The results of the study, spirituality-based leadership exemplified by Pope Francis, include exemplary actions, selfless service, humility, openness to dialogue, and a commitment to social justice. Leadership that can be applied by a nurse is an exemplary attitude, acting selflessly, being humble, and being fair. The conclusion is that leadership based on spiritual values ​​​​from Pope Francis has great potential to provide strong direction in making wise decisions, motivating patients, and building an inclusive and sustainable community for nurses in carrying out their duties.